Methamphetamine Use: A Narrative Review of Adverse Effects and Related Toxicities - Amber N. Edinoff; Sarah E. Kaufman; Keionne M. Green; Daniel A. Provenzano; Jesse Lawson; Elyse M. Cornett; Kevin S. Murnane; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
Methamphetamine has been labeled "America's most dangerous drug" and has received significant public health attention. Stimulant addiction and tolerance are heavily documented in the literature; increasingly larger doses maintain euphoria in short time periods to withstand stimulant tolerance. Stimulant deaths are high in the United States and abroad. Between 2013 and 2019, deaths related to methamphetamine use quadrupled from 3,616 to 16,127. Methamphetamine use increased four-fold from 2015 to 2016. Due to this increase in methamphetamine use and its associated medical complications, the mortality rate associated with methamphetamine use has doubled over the past ten years. Cardiopulmonary symptoms include chest pain, palpitations, and shortness of breath. Methamphetamine-related myocardial infarction can also occur. Central nervous system symptoms include agitation, anxiety, delusions, hallucinations, and seizures. Methamphetamine-induced psychosis may unmask underlying psychiatric disorders. It can also cause cerebral vasculitis, which elicits cortical blindness and ischemic strokes. Methamphetamine-induced neurotoxicity in serotonergic systems is more diffuse, involving the striatum, hippocampus, septum, amygdala, and hypothalamus leading to mood changes, psychosis, and memory impairment. This narrative review will aim to highlight the adverse effects as well as the toxicity that can occur with methamphetamine use.